The Role of Membership Rules in Regional Organizations - Judith Kelley (Asian Development Bank (ADB), 2010)
This paper argues that success in the struggle for regional integration hinges foremost on the degree of heterogeneity among regional states. Regional organizations therefore must consider how to optimize their leverage to forge convergence that will foster agreement and cooperation. To do so, regional organizations can rely on inclusive designs that admit member states and then seek to mold their behavior ex post, or they can use exclusive designs that condition membership on ex ante changes in state behavior. This paper examines the success of these designs in using various ex ante versus ex post tools in soliciting cooperative behavior among regional states, arguing that ex ante tools generally have greater advantages. However, because the advantages vary by issue areas, regions may benefit from creating layers of institutions with different designs. Finally, even after admitting states, regional organizations have options for varying membership rules across different areas of cooperation. Drawing especially on the European experience, the paper considers these various forms of differentiated rules that organizations can use to forge cooperation among different groups of member states despite remaining differences.
hdl:11540/1952
Keywords: F50; F53; F55; 330; Regional integration; international cooperation; membership rules